Analysis of the Possibility of Developing "Earthship" Autonomous Buildings - Mach, Aleksandra (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This paper presents a general technical characteristics of autonomous buildings - earthship, an analysis of the results of surveys of the public`s knowledge and perception of this construction technology compared to the studies presented in the literature, and the development of a SWOT matrix and its analysis in the context of the development and dissemination of the construction of autonomous buildings.
Keywords: autonomous building; earthship; sustainability; waste management; budownictwo autonomiczne; dom z ziemi; zrównoważony rozwój; wykorzystanie odpadów